A Learning Trajectory for Variables Based in Computational Thinking Literature: Using Levels of Thinking to Develop Instruction. Issue 2 (3rd April 2022) - Rich, Kathryn M.; Franklin, Diana; Strickland, Carla; Isaacs, Andy; Eatinger, Donna
ABSTRACT: Background and Context: We explored how learning trajectories (LTs) might be used to design variables instruction. Objective: We aimed to develop an LT for variables and use it to guide curriculum development for fourth graders working in Scratch in an integrated mathematics+CS curriculum. Method: We synthesized learning goals (LGs) and levels of thinking about variables from existing research, then designed instruction to support progress along the levels of thinking while addressing a subset of the LGs. Findings: Our literature synthesis articulated four levels of thinking and eight LGs about variables. Curriculum development allowed us to support movement through the levels of thinking while addressing five LGs in an integrated math+CS course for fourth grade using Scratch. Implications: Our model of curriculum development around levels of thinking can support the creation of customized instructional sequences.